2016
DOI: 10.1017/s1368980016002494
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation of food security among the Batwa of Kanungu, Uganda

Abstract: ObjectiveClimate change is projected to increase the burden of food insecurity (FI) globally, particularly among populations that depend on subsistence agriculture. The impacts of climate change will have disproportionate effects on populations with higher existing vulnerability. Indigenous people consistently experience higher levels of FI than their non-Indigenous counterparts and are more likely to be dependent upon land-based resources. The present study aimed to understand the sensitivity of the food syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(84 citation statements)
references
References 49 publications
3
77
0
Order By: Relevance
“…It has been shown to be a reliable and valid measure of diet when compared with 4-day food diaries. 17 An interviewer-administered version of the questionnaire was used to ensure accurate data entry and provide the opportunity to discuss both quantitative and qualitative aspects of dietary intake with participants.…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown to be a reliable and valid measure of diet when compared with 4-day food diaries. 17 An interviewer-administered version of the questionnaire was used to ensure accurate data entry and provide the opportunity to discuss both quantitative and qualitative aspects of dietary intake with participants.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, Indigenous communities in many countries tend to be more food insecure than their non-Indigenous counterparts [27][28][29]; for example, Indigenous peoples in the United States including American Indians and Alaska Natives were twice as likely to be food insecure compared to non-Indigenous peoples [30]. Around 97% of Indigenous Batwa households in Uganda were found to be food insecure, which was substantially higher than the national Ugandan average of 20% [31]. Furthermore, Indigenous peoples often have close relationships with the environment for subsistence; as such, even subtle changes in the environment can have large impacts on their food security [32,33], including reducing access to, and availability of, Indigenous foods [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, these studies have shown slow annual stunting reduction rate of 0.45% which increases the chances of these children growing into stunted adults and this could partly explain the high proportions and increased odds of stunting in western and central regions seen in this study. An alternative explanation to these ndings could be the fact that Western Uganda is partly inhabited by the Batwa tribe, an indigenous pygmy population who are relatively short (in height) compared to other Ugandans [5,16] and the possibility of migration of stunted women from other regions to the Central and Western regions which are the most economically vibrant regions.…”
Section: Discussionmentioning
confidence: 99%
“…Underweight was de ned as body mass index (BMI) less than (<) 18.5 kg/m 2 while stunting was de ned as height less than (<) 145cm [3,11,20]. Underweight is further classi ed as severe (BMI less than 16.00 kg/m 2 ), moderate (BMI 16.0016.99 kg/m 2 ), and mild (BMI 17.00-18.49 kg/m 2 ).…”
Section: Outcome Variablesmentioning
confidence: 99%
See 1 more Smart Citation